CONFLICT MANAGEMENT STRATEGIES IN IMPROVING THE PERFORMANCE OF THE EDUCATIONAL PERSONNEL TEAM AT SEMARANG STATE UNIVERSITY - Pretty Failasufa Aziza; Ika Widiastuti (Perkumpulan Dosen Program Hibah Indonesia, 2024)
Objective study This is For explain influence strategy management conflict to performance. Conflict can happen on Who just And Where just with No know status, income And position. Strategy manage conflict as Wrong One effort For create performance Good For performance individual employee nor performance team. Population study This is all over power education in UNNES with taking sample use proportional sampling a number 88 sample. Results study prove that hypothesis Which state strategy management conflict influential in a way positive And significant to performance teamwork accepted. Matter This explain that strategy management conflict can give contribution on performance through ability employee in accommodate idea from colleague Work, ability avoid difference opinion with keep your feelings And keep the relationship communication, And do collaboration about work methods